Modern Physics : - Puri, Sanjiv (Alpha Science International Ltd., 2004)
introduces the fundamental concepts pertaining to the basic topics of relativity, quantum mechanics and statistical mechanics along with the important sub-fields of physics, namely, atomic, nuclear and solid state physics. Besides, the technologically important topics of Superconductivity and Optoelectronics, Lasers and Nanoparticles also are introduced to a reasonable extent. The introduction of latest applications, alongwith already established ones, particularly those based on x-rays, lasers, radioactivity and condensed matter form a key feature of the book